Polyphenol rich horseradish root extracts and juice: in vitro antitumor activity and mechanism of action - Petrović, Vidosava; Četojević-Simin, Dragana; Milanović, Maja; Vulić, Jelena; Milić, Nataša (Vojnosanitetski pregled, 2021)
Background/Aim. Plant polyphenols are well known to show antimutagenic, anticarcinogenic, antiviral and antioxidative activity. The aim of this study was to investigate bioactive potential of Armoracia rusticana root juice and extracts: their polyphenol content, as well as in vitro antitumor activity and cell-death mechanism. Methods. Liquid-liquid extraction of polar and non-polar compounds was used and polyphenolic compounds were identified and quantified by high performance liquid chomatography (HPLC) analysis. Antiproliferative activity was examined in vitro on human cervix carcinoma (HeLa), breast adenocarcinoma (MCF7, MDA-MB-231), colon adenocarcinoma (HT-29), lung adenocarcinoma (A549), prostate adenocarcinoma (PC-3), melanocyte carcinoma (Hs 294T), hepatocyte carcinoma (Hep G2), as well as rat hepatocyte carcinoma (H-4-II-E), and normal human fetal lung (MRC-5) cell line using sulforhodamine B assay. The mechanism of cell-death in cell line was determined using Cell Death Detection ELISAPLUS kit. Results. Dichloromethane extracts had the highest content of catechin, p-hydroxybenzoic, syringic and gallic acid (pulp, E1), and epicatechin (juice, E3). The results showed strong and non-selective antiproliferative activity of chloroform and dichloromethane extracts and root juice – highest being towards liver, breast and lung tissue cells. IC50 values of extracts and juice had low range of concentrations (IC50 = 3.49–26.5 µg/mL) and high range of dilutions (IC50 = 418–1,590). High and unfavorable potential of horseradish juice and chloroform juice extract (E4) to induce necrotic cell death was detected. Conclusion. Strong and non-selective in vitro antiproliferative activity of chloroform and dichloromethane extracts and root juice of horseradish was detected, with necrosis as a main mechanism of induced cell death. In order to utilize horseradish root bioactive potential further investigations that will pinpoint active components with more favourable apoptosis/necrosis inducing properties are needed.